Causality Exploration between Interactions of Competition, Efficiency, and Stability and Capital Structure in African Banks - Mauto, Respect Kudzai; Marire, Junious; Khumalo, Sibanisezwe; Malumisa, Sambulo (International Journal of Economics and Financial Issues, 2026)
This study examines the causal relationship between capital structure, measured by the capital–asset ratio (CAR), and the joint dynamics of competition, efficiency, and stability in African commercial banks. Using panel data from 66 banks across 12 African countries over the period 2010–2021, the study employs the two-step system Generalized Method of Moments (GMM) estimator to address endogeneity and dynamic effects. To capture the combined influence of banking market conditions, a composite Competition–Efficiency–Stability Index (CESINDEX) is constructed. The empirical results reveal a bidirectional causal relationship between CESINDEX and CAR, indicating that capital structure both influences and is influenced by the interaction of competition, efficiency, and stability in the banking sector. Robustness checks using an alternative measure of capital structure—the liabilities–asset ratio (LAR)—confirm the consistency of the findings. These results highlight the interdependence between bank capitalization and market dynamics, suggesting that regulatory policies aimed at strengthening bank capital can have broader implications for competitive behavior, operational efficiency, and financial stability. The study contributes to the limited empirical literature on African banking systems and offers valuable insights for policymakers and bank managers seeking to promote a resilient and efficient financial sector.